PERANCANGAN DAN IMPLEMENTASI SISTEM APLIKASI ABSENSI BERBASIS QR CODE DENGAN LOCK GPS - Restu, Restu Iman Jaya Lase; Hutabri, Ellbert (Computer Science and Industrial Engineering, 2022)
The development of technology is so fast, especially in the field of smartphone technology. Software development on smartphones can support work activities for companies or shops. The presence of employees in a company or shop requires a report for administration. Regarding the absence of employees who are still manual and conventional at the Cahaya Elektronik shop, it becomes a problem for shop owners, there is damage to attendance papers, and it has a negative impact on shop owners due to being absent. Likewise with inefficient leave applications which often have a negative impact on shop owners due to negligence. Therefore, the researchers produced a QR Code-based attendance application. This research uses the waterfall method by using Unified Modeling Language (UML) modeling. The QR Code-based attendance application is built by utilizing the justapp platform which produces an attendance system that is able to find out the location of the user or employee's whereabouts, as well as an efficient leave application process. The purpose of this research is to make it easier for employees to take attendance and apply for leave.